2012
DOI: 10.1063/1.3679085
|View full text |Cite
|
Sign up to set email alerts
|

One-step fabrication of L1 FePt nanocubes and rods by cluster beam deposition

Abstract: , "One-step fabrication of L10 FePt nanocubes and rods by cluster beam deposition" (2012 In this work, single crystal L1 0 FePt nanocubes have been successfully produced by a cluster beam deposition technique without the need of post annealing. Particles have been deposited by dc magnetron sputtering using high Ar pressures on both single crystal Si substrates and Au grids for the measurement of magnetic and structural properties, respectively. The nanocubes have a uniform size distribution with an average siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…13 It has also been used for synthesis of rare earth, [9][10][11][12] and rare-earth-free magnetic nanoparticles. [14][15][16] Generally, nanostructures were synthesized with CBD technique by optimizing sputtering power, inert gas ow and aggregation length. Sputtering power is driving force in CBD system to obtain desired crystalline structure.…”
Section: Introductionmentioning
confidence: 99%
“…13 It has also been used for synthesis of rare earth, [9][10][11][12] and rare-earth-free magnetic nanoparticles. [14][15][16] Generally, nanostructures were synthesized with CBD technique by optimizing sputtering power, inert gas ow and aggregation length. Sputtering power is driving force in CBD system to obtain desired crystalline structure.…”
Section: Introductionmentioning
confidence: 99%
“…In some experiments, after having grown the NPs with LPGAS, thermal annealing was performed in-flight, by allowing the NP beam to flow through an oven [96]. In other works, a careful optimization of the design of the magnetron, the sputtering target, and of the parameters governing the sputtering and the NP condensation (sputtering voltage, current density, and inert gas pressure) permitted the direct synthesis of monodispersed FePt NP in the L1 0 phase [93,97,98] (see figure 17).…”
Section: Magnetic Properties Of Metal@oxide Np: Ebmentioning
confidence: 99%
“…This phenomenon is significant not only to our understanding of nature, but also to our current technology as efforts continue to create smaller and smaller devices. Previous studies revealed novel behavior in the optical and magnetic properties as the size of the system is decreased (Andres et al 1989;Schneider et al 1990;Gavrin et al 1990; Akdogan et al 2012Akdogan et al , 2013. Of fundamental importance is the behavior of the Curie temperature in ferromagnetic systems.…”
Section: Introductionmentioning
confidence: 99%